STRATEGIES THAT INCREASE THE LEVEL OF LISTENING COMPREHENSION WHILE LISTENING TO ORAL TEXTS - Mariia Rubtcova; Yulia Varlamova (Universidade Federal de Sergipe, 2019)
The present paper examines the effectiveness of strategy instructional program elaborated for 120 intermediate students with different previous learning backgrounds attending language center in Saint Petersburg.  The objective of the study is to develop program and improve the level of listening comprehension through focusing on potential problems while doing listening tasks. The study either aims at determining and mastering cognitive, metacognitive, social strategies on the part of the students. The authors hypothesize that learners can gain proficiency in using strategies with practice. Strategies can be easily acquired, they facilitate learning, however, number of them are not always transferred to new tasks and used by students as effectively as before when the activity is over. Therefore, systematic strategy instruction component would be important as learners become aware of the learning process and gain the ability to control their own learning through the use of appropriate learning strategies. The authors of the paper have made an attempt to demonstrate that the number of listening comprehension problems reported by the students could be reduced by applying specially designed comprehension activities that assist learners in evaluation of their efforts and assessment of personal achievements. The pilot groups were asked to complete the questionnaires at the beginning and at the end of the course that allowed monitoring the students' progress throughout the course.  At the end of the study, the pilot groups participating in the strategy instructional program were found to be more successful in foreign language comprehension.